Anticancer activity of Stichopus vastus extract against MCF-7 and HeLa cells from Natuna waters - Sukmiwati, Mery; Nurjanah, Nurjanah; Diharmi, Andarini; Putri, Indah Prasetya (Faculty of Pharmacy, Universitas Pancasila, 2025)
Sea cucumbers (Stichopus vastus) contain bioactive compounds with potential anticancer properties, making them a promising alternative raw material for pharmaceutical development. This study aimed to isolate and fractionate bioactive compounds from S. vastus and evaluate their anticancer activity against MCF-7 and HeLa cell lines. Isolation was performed using Thin Layer Chromatography (TLC), and cytotoxic activity was assessed in vitro using the MTT assay. Phytochemical screening revealed the presence of steroids, terpenoids, and saponins. IC₅₀ values were calculated through linear regression analysis. The methanol extract exhibited IC₅₀ values of 13.50 µg/mL (HeLa) and 17.25 µg/mL (MCF-7), indicating active anticancer potential. The n-hexane fraction showed IC₅₀ values of 10.09 µg/mL (HeLa) and 15.11 µg/mL (MCF-7), also categorized as active. Notably, the ethyl acetate fraction demonstrated superior activity, with an IC₅₀ of 7.00 µg/mL against HeLa (very active) and 13.32 µg/mL against MCF-7 (active). These findings suggest that the ethyl acetate fraction of S. vastus holds significant promise as an anticancer agent, particularly against HeLa cells.